Proceso atención de enfermería en gestante de 36 semanas con púpura trombocitopénica idiopática. - Vera Rodriguez, Evelyn Katiusca (2022)
Immune thrombocytopenic purpura is characterized by a decrease in blood platelets with a count below 100 x 10*9/L, which corresponds to 5% of all causes of thrombocytopenia, it is also extremely rare and occurs in 0. 1% of pregnancies. For the study, it was possible to review different bibliographic sources where the idiopathic thrombocytopenic purpura is deepened, this is how it was possible to create an enriched theoretical framework with definitions, epidemiology, risk factors, diagnosis and treatments of the disease. During the development of the investigation, it was possible to apply a nursing care process in a pregnant woman, using the method of observation and interview implemented through physical examination and anamnesis, respectively, in addition, it was possible to identify through correct handling of the history. clinical history, previous pathological history of said disease, nursing interventions were applied such as peripheral intravenous cannulation, administration of crystalloid solutions, urinary catheterization and hydroelectrolytic control through the use of fluid balance to eradicate future complications that could put at risk to the maternal-fetal dyad. As a culmination of the study, it was possible to obtain the fulfillment of the objectives set from the beginning of the same, which helped to guarantee the well-being of the patient and her baby.